If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 12) + 7(x + -5) = 4x + -56 Reorder the terms: 2(12 + x) + 7(x + -5) = 4x + -56 (12 * 2 + x * 2) + 7(x + -5) = 4x + -56 (24 + 2x) + 7(x + -5) = 4x + -56 Reorder the terms: 24 + 2x + 7(-5 + x) = 4x + -56 24 + 2x + (-5 * 7 + x * 7) = 4x + -56 24 + 2x + (-35 + 7x) = 4x + -56 Reorder the terms: 24 + -35 + 2x + 7x = 4x + -56 Combine like terms: 24 + -35 = -11 -11 + 2x + 7x = 4x + -56 Combine like terms: 2x + 7x = 9x -11 + 9x = 4x + -56 Reorder the terms: -11 + 9x = -56 + 4x Solving -11 + 9x = -56 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -11 + 9x + -4x = -56 + 4x + -4x Combine like terms: 9x + -4x = 5x -11 + 5x = -56 + 4x + -4x Combine like terms: 4x + -4x = 0 -11 + 5x = -56 + 0 -11 + 5x = -56 Add '11' to each side of the equation. -11 + 11 + 5x = -56 + 11 Combine like terms: -11 + 11 = 0 0 + 5x = -56 + 11 5x = -56 + 11 Combine like terms: -56 + 11 = -45 5x = -45 Divide each side by '5'. x = -9 Simplifying x = -9
| (8x-y-7)(6x)= | | x^3=41 | | 5y+36=10y+6 | | 0=x^3-3x-6 | | 4(2r+5)=6(r-2) | | 9-11x-7-10x=5 | | 6.1-r=3.4 | | 24d+40de= | | 4(z-3)+z=-2 | | -3(y-4)=18 | | -(9x-9)+9x= | | -3(7+5n)=-96 | | -1/3(2b-6) | | 3+4x+3=-2 | | X(7x-3)=(7x+8)(x-1) | | 7(2x-3)=3+2(x+5)+7 | | 11(-9-2x)=-(12x+11) | | i+30=28 | | 4(-5+x)=48 | | 3x+8=(6-x) | | 2(x-16)-5(x-3)=18 | | 6[x-10]+8=26 | | 7z+17=6z+8 | | 16x+5=-37 | | (x+9)(x-3)=(x+1)(x+1) | | [n/10]=3 | | 8-(3+b)=b+-9 | | -[p-4]+9=8 | | -3r-6r=-9 | | 3(x-4)-4(3-x)=x+3-(x-5) | | 5(x^2-x-12)=0 | | N/-0.5=13 |